Some Dilemmas and Challenges in Academic Translation/Interpretation Teaching - Mirjana M. Daničić (University of Belgrade, Teacher Education Faculty, 2018)
The paper presents the introduction of new master translation courses at the Faculty of Philology in Belgrade. It describes the curricula for the translation courses in Translatology in the main study programme Language, Literature, Culture, as well as for a specialized translationand interpretation-oriented study programme Master in Conference Interpreting and Translation (MCIT). Both programmes have been conceived in line with the contemporary theories of translation and abide by the best translation teaching strategies of top European universities. Their aim is not only to develop students' translational competencies to adequately convey words and their meanings from the source language to the target language, but also to get thorough background knowledge of the subject matter along with the knowledge of cultural and social factors which can influence possible meanings, especially when it comes to community translation. The paper also tries to show how such a transformation of the traditional approach to translation teaching can consequently lead to the transformation of a notion of translator from someone who converts words from one language to another to an intellectual worker with academic professional training.